Smith and Nesi's Ophthalmic Plastic and Reconstructive Surgery - Nesi, Frank A.; Gladstone, Geoffrey J.; Levine, Mark R.; Black, Evan H. (Springer New York, 2012)
Smith and Nesi's Ophthalmic Plastic and Reconstructive Surgery, Third Edition has taken the best of the field's classic reference text and expanded upon it, continuing its reputation as the foremost guide to the subspecialty. Every practitioner of plastic and reconstructive surgery will find useful information in this comprehensive, in-depth text, including an update on the changes and advances of the last several years and a new section on pediatric consideration. Detailed chapters on ophthalmic anatomy are also included, as well as sections on eyelid dermatology, socket surgery, and cosmetic surgery. Every consideration has been made by Dr. Nesi and his co-editors to cover every aspect important to the ophthalmic plastic surgeon. Features: Fully updated and revised edition of Smith's Ophthalmic Plastic and Reconstructive Surgery Comprehensive text with detailed chapters that cover all aspects of the subject matter More than 1700 figures and 77 chapters